Non-alcoholic beverage marketing in 100 highest grossing movies in 2010-2014. Issue 4 (3rd April 2018) - Cockburn, Nicole; Schubert, Lisa; Nguyen, Nam-Phuong Quoc; Ford, Pauline
Abstract : Purpose: Australian sales of hyperpalatable beverages (HPB) (a term used to describe naturally or artificially sweet beverages) have followed a consistent upward trend since 2000. The purpose of this paper is to examine HPB brand placements in the top 20 annual highest grossing movies in Australia in 2010-2014. Design/methodology/approach: A content analysis was undertaken on the 20 highest grossing movies annually from 2010 to 2014. Movies were analysed according to the prevalence and portrayal of branded beverages. Findings: In total, 35 per cent of movies contained an HPB brand placement. Movies were more likely to be classified M, MA15+, R/R18+, and categorised as comedy, or action/adventure genre. Soft drinks were the most prevalent category (60.9 per cent), and Coca Cola Company manufactured 40.6 per cent of the brands that were embedded throughout the movies. Originality/value: This study revealed some of industry's non-direct marketing strategies through HPB placement in movies. Findings suggest that further scrutiny is needed of the relatively underresearched medium of beverage advertising.